Pengaruh Investasi Terhadap Pertumbuhan Dan Pembangunan Ekonomi Dalam Perspektif Ekonomi Islam - Zaharah, Rita; Nur, Efa Rodiah; Santoso, Rudi (ASAS, 2022)
Growth and economic development are very closely related. Economic growth is an important indicator in carrying out economic development in a country. Some economists pay special attention to capital as one of the factors that influence economic growth. One of the efforts that can be made by the government in encouraging economic growth is to seek capital or sources of financing, one of which is through investment both domestically and abroad. Like other developing countries, Indonesia relies heavily on investment to support the financing of its economic development, both through foreign and domestic investment. Islam strongly recommends investment from both a non-economic and an economic point of view. Viewed from an economic point of view, investment is a commitment to sacrifice funds in a definite amount at the present time to gain the profits in future, of course, with the guidance of the Shari'a. Investment activities are part of Muamalah activities that are permissible unless there is an implication of the argument from the Qur'an and al-Hadith which prohibits it either explicitly or implicitly.Keywords: Investment, Development Islamic Economics, and Economic Growth